2022
DOI: 10.3389/fenrg.2022.1003449
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the pump mode and turbine mode performance of a large vaned-voluted centrifugal pump

Abstract: Large vaned-voluted centrifugal pump is a general machine used for large-scale water diversion. As a vane-type hydraulic machinery, it also has the ability of reversible operation. With the introduction of policies to reduce carbon emissions, the proportion of unstable new energy use has increased. The existing large centrifugal pump unit can realize the function of reverse power transfer. For peak shaving and valley filling of power grid, it has high feasibility and economy. In this paper, a large vaned-volut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…These correlation coefficients validate the practicality of the proposed correlations within the specified range of hydraulic data. 20) and (21). The deviation between the two techniques varies across different sites.…”
Section: Correlation Between Site and Pump Hydraulic Datamentioning
confidence: 99%
See 4 more Smart Citations
“…These correlation coefficients validate the practicality of the proposed correlations within the specified range of hydraulic data. 20) and (21). The deviation between the two techniques varies across different sites.…”
Section: Correlation Between Site and Pump Hydraulic Datamentioning
confidence: 99%
“…Considering the small deviations and the high accuracy of the proposed methodology, it can be concluded that the derived correlations provide a practical and reliable means of estimating the pump flow rate and head based on the available site hydraulic data. 20) and (21). The deviation between the two techniques varies across different sites.…”
Section: Correlation Between Site and Pump Hydraulic Datamentioning
confidence: 99%
See 3 more Smart Citations